The Graduation of Program Keluarga Harapan Beneficiaries: Analysis of Driving Factors - Prafianti , Finda; Prananta Moeis, Jossy (Research Horizon, 2025)
This study aims to identify and analyze key factors that contribute to the successful graduation of beneficiary households from the social assistance program PKH (Program Keluarga Harapan) or Family Hope Program, as well as to provide policy recommendations based on research findings related to factors influencing program graduation. Using logistic regression analysis, this research utilizes cross-sectional data from the 2014 Indonesian Family Life Survey (IFLS). The study reveals that variables associated with the graduation status of PKH beneficiaries include having at least one child attending high school, participation in community empowerment activities, the age and education level of the household head, the number of employed household members, and household size. These findings offer valuable insights for government policymakers in designing social assistance policies that promote the long-term well-being of beneficiaries through more inclusive Conditional Cash Transfer (CCT) programs. In this regard, PKH social assistance should not only serve as a short-term poverty alleviation measure but also as a long-term and sustainable solution.